BNT162b2 mRNA COVID-19 vaccine and booster in patients with autoimmune rheumatic diseases: a national cohort study. Issue 7 (13th April 2022) - Bieber, Amir; Sagy, Iftach; Novack, Lena; Brikman, Shay; Abuhasira, Ran; Ayalon, Snait; Novofastovski, Irina; Abu-Shakra, Mahmoud; Mader, Reuven
Abstract : Introduction: Emerging evidence supports the immunogenic response to mRNA COVID-19 vaccine in patients with autoimmune rheumatic diseases (ARD). However, large-scale data about the association between vaccination, and COVID-19 outcomes in patients with ARD is limited. Methods: We used data from Clalit Health Services, which covers more than half of the population in Israel. Patients with ARD older than 18 were included between 20 December 2020 and 30 September 2021, when the BNT162b2 mRNA COVID-19 vaccine, and later a third booster dose, were available. The primary outcome was a documented positive SARS-CoV-2 PCR test. We used a Cox regression models with vaccination status as time-dependent covariate and calculated the HR for the study outcome. Results: We included 127 928 patients with ARD, of whom, by the end of the study follow-up, there were 27 350 (21.3%) unvaccinated patients, 31 407 (24.5%) vaccinated patients and 69 171 (54.1%) patients who also received a third booster-dose. We identified 8470 (6.6%) patients with a positive SARS-CoV-2 PCR test during the study period. The HR for SARS-CoV-2 infection among the vaccination group was 0.143 (0.095 to 0.214, p<0.001), and among the booster group was 0.017 (0.009 to 0.035, p<0.001). Similar results were found regardless of the type of ARD group or antirheumatic therapy. Conclusion: Our results indicate that both the BNT162b2 mRNA COVID-19 vaccine and the booster are associated with better COVID-19 outcomes in patients with ARD.